Analisa Rekrutmen, Seleksi dan Penempatan Kru Terhadap Kinerja Kru Kapal di PT. MCS Internasional Jakarta - Sundarti Sundarti; Vivid Dekanawati (Sekolah Tinggi Maritim Yogyakarta, 2020)
Employees are valuable property owned by each agency / company. Every company must get employees in accordance with the objectives of the company and place employees in accordance with their capabilities. To achieve company goals, a good recruitment, selection and placement process is needed. Crew of the ship or often called Seafarers is an asset of human resources working on the ship. In the role of the shipping company the shipping crew is the most important thing carried by each shipping company. This research is a qualitative research with a descriptive-analytical approach with the study of literature studies including internet website searches and secondary data analysis, namely by reviewing some references about the process of recruitment, selection and placement of employees on the ship or called the crew. PT. MCS International has well implemented the recruitment, selection and placement process of the crew so that the company's goals can be achieved.